Wind tunnel study of the effect of planting Haloxylon ammodendron on aeolian sediment transport. (August 2021) - Fu, Guiquan; Xu, Xianying; Qiu, Xiaona; Xu, Gaoxing; Shang, Wen; Yang, Xuemei; Zhao, Peng; Chai, Chengwu; Hu, Xiaoke; Zhang, Yunian; Wang, Qiangqiang; Zhao, Chuanyan
Abstract : Revegetation is a widely used way to minimise aeolian sediment transport in desertified land. An optimal vegetation density and planting pattern reduces the economic investment for revegetation and competition for limited water resources. This study aimed to ascertain the effects of vegetation density and planting pattern on aeolian sediment transport at the regional scale. A series of wind tunnel tests were implemented with artificial shrubs representing Haloxylon ammodendron . These tests were designed with three planting densities (i.e., 600 plants ha −1, 1200 plants ha −1, and 1650 plants ha −1 ) and four patterns (uniform distribution, random distribution, two rows/one belt, and one row/one belt pattern). Geostatistical interpolation methods available in ArcGIS were used to analyse the spatial variation of sand heights. Vegetation density and planting pattern and their interaction all significantly affected the aeolian sediment transport but vegetation density had the greatest impact. With increasing density of vegetation, wind erosion rate decreased significantly following quadratic function, and wind erosion still occurred around the artificial shrubs regardless of vegetation density and planting pattern. For wind erosion rate, erosion and deposition area, the uniform distribution pattern had little protective benefit at the three planting densities, whilst the combinations of the random distribution pattern with 600 plants ha −1, two rows/one belt pattern with 1200 plants ha −1, and one row/one belt pattern with 1650 plants ha −1 had the best protective benefit in controlling the aeolian sediment transport. Highlights: Influence of vegetation density and pattern at a regional scale investigated. Geostatistical interpolation used to analyse the spatial variation of sand depth. Density and pattern of artificial shrubs significantly affected sediment transport. Wind erosion still occurred around shrubs regardless of vegetation density and pattern. Optimal planting pattern for reducing aeolian transport different in the 3 densities.